Sources of distress for physicians and nurses working in Swiss neonatal intensive care units (Swiss Medical Weekly, 2017)
BACKGROUND Medical personnel working in intensive care often face difficult ethical dilemmas. These may represent important sources of distress and may lead to a diminished self-perceived quality of care and eventually to burnout. AIMS OF THE STUDY The aim of this study was to identify work-related sources of distress and to assess symptoms of burnout among physicians and nurses working in Swiss neonatal intensive care units (NICUs). METHODS In summer 2015, we conducted an anonymous online survey comprising 140 questions about difficult ethical decisions concerning extremely preterm infants. Of these 140 questions, 12 questions related to sources of distress and 10 to burnout. All physicians and nurses (n = 552) working in the nine NICUs in Switzerland were invited to participate. RESULTS The response rate was 72% (398). The aspects of work most commonly identified as sources of distress were: lack of regular staff meetings, lack of time for routine discussion of difficult cases, lack of psychological support for the NICU staff and families, and missing transmission of important information within the caregiver team. Differences between physicians’ and nurses’ perceptions became apparent: for example, nurses were more dissatisfied with the quality of the decision-making process. Different perceptions were also noted between staff in the German- and French- speaking parts of Switzerland: for example, respondents from the French part rated lack of regular staff meetings as being more problematic. On the other hand, personnel in the French part were more satisfied with their accomplishments in the job. On average, low levels of burnout symptoms were revealed, and only 6% of respondents answered that the work-related burden often affected their private life. CONCLUSIONS Perceived sources of distress in Swiss NICUs were similar to those in ICU studies. Despite rare symptoms of burnout, communication measures such as regular staff meetings and psychological support to prevent distress were clearly requested.